Repositioning Women from Policy Objects to Agents of Change: Challenges in Stunting Prevention in Pohuwato Regency - Abbas, Syahrawati; Tahir, Arifin; Aneta, Yanti; Dama, Hais (Universitas Teuku Umar, 2025)
This study explores the challenges of handling stunting using a women’s empowerment approach in Pohuwato Regency. The main objective is to analyze the extent to which women at risk of stunting can play an active role in prevention efforts and to evaluate the effectiveness of government support in fostering their independence. A descriptive qualitative method was employed, utilizing observation, in-depth interviews, and documentation. Informants included women vulnerable to stunting and stakeholders in empowerment and stunting prevention programs. Findings reveal that although institutional support is relatively adequate, women’s roles remain passive, with low authority, self-confidence, and competence to act independently. Their reliance on top-down assistance limits initiative and decision-making capacity. Furthermore, a lack of practical skills hampers their ability to utilize abundant local resources—particularly in agriculture and biological sectors—for economic and nutritional improvements. The study concludes that women are still treated more as policy objects than empowered agents of change. To address this, empowerment strategies must prioritize capacity building, participatory planning, and the transformation of women into active decision-makers. Strengthening multi-stakeholder collaboration and encouraging program ownership are critical to achieving sustainable stunting prevention efforts. This research contributes to gender-transformative public health policies by positioning women as central actors in community-based interventions.